Seasonal hydrologic and geologic forcing drive hot spring geochemistry and microbial biodiversity. (10th June 2021) - Colman, Daniel R.; Lindsay, Melody R.; Harnish, Annette; Bilbrey, Evan M.; Amenabar, Maximiliano J.; Selensky, Matthew J.; Fecteau, Kristopher M.; Debes, Randall V.; Stott, Matthew B.; Shock, Everett L.; Boyd, Eric S.
Summary: Hot springs integrate hydrologic and geologic processes that vary over short‐ and long‐term time scales. However, the influence of temporal hydrologic and geologic change on hot spring biodiversity is unknown. Here, we coordinated near‐weekly, cross‐seasonal (~140 days) geochemical and microbial community analyses of three widely studied hot springs with local precipitation data in Yellowstone National Park. One spring ('HFS') exhibited statistically significant, coupled microbial and geochemical variation across seasons that was associated with recent precipitation patterns. Two other spring communities, 'CP' and 'DS', exhibited minimal to no variation across seasons. Variability in the seasonal response of springs is attributed to differences in the timing and extent of aquifer recharge with oxidized near‐surface water from precipitation. This influx of oxidized water is associated with changes in community composition, and in particular, the abundances of aerobic sulfide‐/sulfur‐oxidizers that can acidify waters. During sampling, a new spring formed after a period of heavy precipitation and its successional dynamics were also influenced by surface water recharge. Collectively, these results indicate that changes in short‐term hydrology associated with precipitation can impact hot spring geochemistry and microbial biodiversity. These results point to potential susceptibility of certain hot springs and their biodiversity to sustained, longer‐term hydrologic changes.